Effects of coaches’ feedback on psychological outcomes in youth football: an intervention study - Berntzen, Iben; Lagestad, Pål (Frontiers in Sports and Active Living, 2025)
IntroductionThe purpose of this study was to examine how feedback from the coach influences football players' experiences of well-being, mastery, pleasure, satisfaction, development, being seen by the coach, and motivation in two different groups.MethodsThe study used an intervention with a crossover experimental approach, where 95 players aged 14–18 that participated in sports clubs and specialized football classes in a town in Mid-Norway, participated in the same organized training session with the same coach in every session—one without feedback and one with feedback from the coach, answering a questionnaire after each training session. The questionnaire was developed with a total of seven questions with high face validity for each of the variables. The study was approved by the Norwegian data protection agency, and a written informed consent for participation in this study was provided by the participants' legal guardians/next of kin. Wilcoxon nonparametric tests were used to examine differences between the session without and the session with feedback among players in the two groups for each variable.ResultsAnalyzing all players, the results showed that when feedback was given, it led to a significant increase in mastery, the experience of being seen by the coach, and motivation, compared to the same training session when they did not receive feedback. Furthermore, analyzing only players who participated in sports studies with a specialization in football, the results showed that giving feedback led to a significant increase in well-being, pleasure, satisfaction, and development. Finally, analyzing only players who participated in sports teams and did not specialize in football in sports programs showed that when feedback was given, it led to a significant increase in, the experience of being noticed by the coach, and motivation—but a decrease in development, compared to the same training session when they did not receive feedback.DiscussionThis study introduces a unique and novel intervention approach focusing on the effects of feedback. The findings suggest that football coaches' feedback has a positive outcome for several psychological factors of young players. The findings of the study highlight the importance of football coaches' feedback.